Graphene performs the role of an electron donor in covalently interfaced porphyrin-boron azadipyrromethene dyads and manages photoinduced charge-transfer processes. Issue 40 (6th October 2022) - Canton-Vitoria, Ruben; Alsaleh, Ajyal Z.; Rotas, Georgios; Nakanishi, Yusuke; Shinohara, Hisanori; D′ Souza, Francis; Tagmatarchis, Nikos
Abstract : Graphene-based hybrid (ZnP-azaBDP)-graphene was synthesized, comprehensively characterized and found to manage energy transfer processes, yielding upon illumination (ZnP-azaBDP˙ − )-graphene˙ + charge-separated state. Abstract : Herein, we introduced the versatility of free-base and zinc-metallated porphyrin (H2 P and ZnP, respectively) to combine with boron azadipyrromethene (azaBDP) NIR absorbing species, for extending their photophysical interest and covalently anchored onto graphene. In particular, the covalent functionalization of graphene with those H2 P-azaBDP and ZnP-azaBDP dyads ensured an invariable structure, in which both chromophores and graphene are in intimate contact, free of aggregations and impurities. Both H2 P-azaBDP and ZnP-azaBDP dyads were found to perform energy transfer processes between the chromophores, however, only ZnP-azaBDP confirmed additional charge separation between the chromophores yielding the ZnP˙ + -azaBDP˙ − charge-separated state. On the other hand, graphene in (H2 P-azaBDP)-graphene and (ZnP-azaBDP)-graphene hybrids was found to act as an electron donor, yielding (H2 P-azaBDP˙ − )-graphene˙ + and (ZnP-azaBDP˙ − )-graphene˙ + charge-separated states at an ultrafast timescale. The creation of such donor–acceptor systems, featuring graphene as an electron donor and Vis-to-NIR electron-acceptor dyads, expands their utility when considered in optoelectronic applications.